Flood Modeling Analysis of the Cokroyasan Watershed in Bayan District, Purworejo Regency Using HEC-RAS Software - Muhammad Rizky Fajar; Sely Novita Sari; Anggi Hermawan (G-Tech: Jurnal Teknologi Terapan, 2025)
Floods are a frequent natural disaster in Indonesia. Heavy rainfall and poor watershed management make the Cokroyasan River Basin (DAS), Bayan District, Purworejo Regency, especially susceptible. The purpose of this study is to analyze the flood inundation area and calculate the peak discharge in the Cokroyasan Watershed using satellite rainfall data and the Digital Elevation Model (DEM). The study calculates the highest water flow during floods using the Nakayasu Synthetic Unit Hydrograph (HSS) method and examines the water flow with HEC-RAS and ArcGIS to create maps showing areas that could flood. The results showed that, using the Log Pearson Type III distribution, the design rainfall for a 25-year return period with a flow coefficient of 0.288 was 117.6711 mm. The maximum flood discharge, as determined by the Nakayasu HSS, was 1684.028 m³/second. Hydraulic analysis was able to map the region of floods based on land cover, covering 16,200 km² in total. 4,961 km² were covered the low flood depth category (0–1 m), 3,175 km² the medium inundation (1–3 m), and 8,061 km² the high inundation (>3 m). The results of the simulation might lead to a more effective approach for managing and reducing the danger of flooding.